The Association of Hematological Parameters in Early and Middle Pregnancy with the Risk of Gestational Diabetes Mellitus - Duo, Yanbei; Song, Shuoning; Qiao, Xiaolin; Zhang, Yuemei; Xu, Jiyu; Zhang, Jing; Peng, Zhenyao; Chen, Yan; Nie, Xiaorui; Sun, Qiujin; Yang, Xianchun; Wang, Ailing; et al. (Diabetes, metabolic syndrome and obesity, 2024)
Gestational diabetes mellitus (GDM) is a condition of glucose intolerance, which may be accompanied with inflammation. The levels of hematological parameters during pregnancy can reflect inflammatory conditions in pregnant women. This study aims to describe the dynamic change of blood cell parameters from the first trimester (6-12 weeks of gestation) to the second trimester (24-28 weeks of gestation) and to investigate the associations of these biomarkers with the risk of GDM. This study was a prospective double-center study conducted in Beijing, China (clinical trial number: NCT03246295). Hematological parameters were tested four times during the follow-up. Logistic regression analysis and Receiver Operating Characteristic (ROC) curve analysis were used to explore the association and predictive ability of hematological parameters for GDM. There were 258 of 1027 pregnant women in our study developed GDM. Among the 1027 pregnant women, white blood cells (WBC) gradually increased, and red blood cells (RBC), hemoglobin (HGB), and platelet (PLT) tended to decrease from the first trimester to second trimester. After adjusting for confounding factors, higher levels of RBC, HGB, and PLT in both early and middle pregnancy were positively associated with GDM risk, whereas the level of WBC was associated with GDM risk only in early pregnancy. WBC, RBC, HGB, and PLT in early and middle pregnancy were all correlated with fasting insulin (FINS) in early pregnancy. Higher levels of hematological parameters in early and middle pregnancy were associated with glucose metabolism in early pregnancy and the subsequent risk of GDM.